New species of Cerambycinae and Lamiinae from Ecuador and Honduras, with transference of a species of Rhinotragini (Coleoptera, Cerambycidae) - Vlasak, Josef; Santos-Silva, Antonio (Zootaxa, 2020)
Three new species are described from Ecuador: Scythropopsis granitica (Lamiinae, Acanthoderini); Apeba danielvlasaki (Lamiinae, Hemilophini); and Giesberteclipta unicolor (Cerambycinae, Rhinotragini). Two new species are described from Honduras: Anelaphus rotundus (Cerambycinae, Elaphidiini); and Euderces hefferni (Cerambycinae, Tillomorphini). A key to species of Apeba Martins & Galileo, 1991, and Giesberteclipta Santos-Silva et al., 2012 are provided. Euderces hefferni sp. nov. is included in a previous key. Rashelapso morrisoni Bezark & Santos-Silva, 2016 is transferred to Giesberteclipta. The holotype of Anelaphus subinermis Linsley, 1957 is illustrated for the first time.